FDA Approval Summary: Sotorasib for KRAS G12C -Mutated Metastatic NSCLC - Nakajima, Erica C.; Drezner, Nicole; Li, Xiaoxue; Mishra-Kalyani, Pallavi S.; Liu, Yajun; Zhao, Hong; Bi, Youwei; Liu, Jiang; Rahman, Atiqur; Wearne, Emily; Ojofeitimi, Idara; Hotaki, Lauren Tesh; et al. (Clinical cancer research, 2022)
On May 28, 2021, the FDA granted accelerated approval to sotorasib (Lumakras, Amgen) for the treatment of adults with advanced non–small cell lung cancer (NSCLC) with a Kirsten rat sarcoma proto-oncogene (KRAS) G12C mutation who have received at least one prior systemic therapy. The approval was based on CodeBreaK 100 (Study 20170543), a dose-escalation and dose-expansion trial in patients with an advanced, KRAS G12C-mutated, solid tumor. The overall response rate (ORR) observed in patients with KRAS G12C-mutated NSCLC treated with sotorasib (n = 124) was 36% [95% confidence interval (CI), 28–45]. The median duration of response was 10.0 months (95% CI, 6.9–not estimable). The most common adverse reactions (≥20%) were diarrhea, musculoskeletal pain, nausea, fatigue, hepatotoxicity, and cough. This is the first approval of a targeted therapy for KRAS G12C-mutated NSCLC. Because of pharmacokinetic data and ORRs of patient cohorts who took sotorasib at lower doses in the dose-escalation portion of CodeBreaK 100, a dose comparison study is being conducted as a post-marketing requirement.